How We Got Here: A Historical Look at the Academic Teaching Library and the Role of the Teaching Librarian - Susan Andriette Ariew (Communications in Information Literacy, 2014)
This paper outlines a brief history of the academic teaching library and, in consequence, it examines the changing role of librarians. As part of that history, the paper also discusses distinctions among various terms used to describe instructional activities in teaching libraries, such as "bibliographic instruction" and "information literacy." Finally, amidst the renewed debates about the definition of information literacy and the Information Literacy Competency Standards, it attempts to answer the question, "What is a teaching Library?"